Divorce Lawsuit against Unrecorded Marriages Post Sema Number 3 Year 2018 - Purba, Mariah SM; Nainggolan, Rosita; Hermes, Christian Daniel; Sinaga, Dhea Rosarni (Budapest International Research and Critics University, 2024)
Issuance of Supreme Court Circular Letter (SEMA) No. 3 of 2018 which states that